2008
DOI: 10.1084/jem.20071658
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the BH3-only protein Bmf impairs B cell homeostasis and accelerates γ irradiation–induced thymic lymphoma development

Abstract: Members of the Bcl-2 protein family play crucial roles in the maintenance of tissue homeostasis by regulating apoptosis in response to developmental cues or exogenous stress. Proapoptotic BH3-only members of the Bcl-2 family are essential for initiation of cell death, and they function by activating the proapoptotic Bcl-2 family members Bax and/or Bak, either directly or indirectly through binding to prosurvival Bcl-2 family members. Bax and Bak then elicit the downstream events in apoptosis signaling. Mammals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
162
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(172 citation statements)
references
References 45 publications
(106 reference statements)
9
162
0
Order By: Relevance
“…Following exposure to 1.5 Gy γ-irradiation weekly for 4 weeks, mice typically succumb to thymic lymphoma around 150-200 days. In this experimental model, NOXA and BMF have been shown to suppress lymphoma development, 110,111 while the role of BAD remains contentious with one report describing accelerated thymic lymphomagenesis in BAD-deficient mice while another publication reported no effect. 54,55 Possible explanations for the discrepancy might include differences in γ-radiation dosing and schedule used or differences in genetic background (C57BL/6 55 versus complicated mixed background 54 ).…”
Section: Mcl1mentioning
confidence: 97%
See 1 more Smart Citation
“…Following exposure to 1.5 Gy γ-irradiation weekly for 4 weeks, mice typically succumb to thymic lymphoma around 150-200 days. In this experimental model, NOXA and BMF have been shown to suppress lymphoma development, 110,111 while the role of BAD remains contentious with one report describing accelerated thymic lymphomagenesis in BAD-deficient mice while another publication reported no effect. 54,55 Possible explanations for the discrepancy might include differences in γ-radiation dosing and schedule used or differences in genetic background (C57BL/6 55 versus complicated mixed background 54 ).…”
Section: Mcl1mentioning
confidence: 97%
“…150,151 Furthermore, BMF as well as BIM are critical for the killing of non-transformed lymphoid cells as well as certain lymphoma cells by inhibitors of histone deacetylases. 110,135 BIM (with BAD and BMF also contributing) is critical for the killing of tumour cells that are dependent on oncogenic kinases by therapeutic agents that block their activity, such as inhibitors of MEK (acting downstream of mutant B-RAF in melanoma or colon carcinoma), 152 EGFR (lung cancer), [153][154][155] BCR-ABL (CML) 156,157 and VEGFR signalling (tumour angiogenesis). 158 Notably, a gene polymorphism that impairs the expression of BIM was found to explain the de novo resistance of BCR-ABL-driven CML to Gleevec and mutant EGFR-driven lung cancer to Iressa/ Tarceva in East Asian populations.…”
Section: The Role Of the Bcl-2-regulated Apoptotic Pathway In Cancer mentioning
confidence: 99%
“…Generation and genotyping of vav-bcl-2 tg, bmf À/À , bim À/À , puma À/À , noxa À/À and bad À/À mice has been described previously (Bouillet et al, 1999;Labi et al, 2008;Ogilvy et al, 1999;Ranger et al, 2003;Villunger et al, 2003). All mice were maintained on a C57BL/6 background.…”
Section: Micementioning
confidence: 99%
“…Moreover, 40% of human Burkitt's lymphomas fail to express PUMA (Garrison et al 2008), and loss of PUMA can also (like loss of BIM) accelerate lymphoma development in Em-MYC transgenic mice (Garrison et al 2008;Michalaket al 2009). In addition, loss of the BH3-only proteins NOXA (Michalak et al 2010) and BMF (Labi et al 2008) as well as loss of BAX (Eischen et al 2001) were found to promote development of lymphoma in different experimental mouse models, but so far deregulation of these genes has not been detected in human cancers. As mentioned above, defects in apoptosis by themselves are not potently transforming.…”
Section: Tumor Suppression By Apoptosismentioning
confidence: 99%